2011
DOI: 10.4148/2378-5977.2908
|View full text |Cite
|
Sign up to set email alerts
|

Administration of human chorionic gonadotropin at embryo transfer induced ovulation of a first-wave dominant follicle and increased progesterone and transfer pregnancy rates

Abstract: Administration of human chorionic gonadotropin at embryo transfer induced ovulation of a first-wave dominant follicle and increased progesterone and transfer pregnancy rates AbstractEmbryo transfer (ET) has become more widespread in recent years as a way to improve cattle genetics. According to the annual statistical survey of the American Embryo Transfer Association, more than 200,000 fresh and frozen bovine embryos were transferred in 2008. But despite advancements in reproductive technologies that have occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Beltman et al (2009a) found that supplementing beef heifers with exogenous P4 during metoestrus (P <0.04) or early dioestrus (P< 0.06) had a positive relationship with embryo survival rates. Similar results were described by Wallace et al (2011) who found significantly higher pregnancy rates in P4-supplemented beef heifers treated with human chorionic gonadotropin (hCG 1000 IU) compared to non-treated animals (66.3 vs. 55.5%, respectively, P< 0.001). In the experiment of Beltman et al (2009a) the embryo length assessed at Day 25 was similar in treated and non-treated heifers (29.5 vs. 30.2 cm, respectively).…”
Section: Role Of Progesterone On Embryo Development and Survivalsupporting
confidence: 77%
See 1 more Smart Citation
“…Beltman et al (2009a) found that supplementing beef heifers with exogenous P4 during metoestrus (P <0.04) or early dioestrus (P< 0.06) had a positive relationship with embryo survival rates. Similar results were described by Wallace et al (2011) who found significantly higher pregnancy rates in P4-supplemented beef heifers treated with human chorionic gonadotropin (hCG 1000 IU) compared to non-treated animals (66.3 vs. 55.5%, respectively, P< 0.001). In the experiment of Beltman et al (2009a) the embryo length assessed at Day 25 was similar in treated and non-treated heifers (29.5 vs. 30.2 cm, respectively).…”
Section: Role Of Progesterone On Embryo Development and Survivalsupporting
confidence: 77%
“…However, when the length was assessed earlier, shortly after MRP (Day 16), the embryos recovered from P4-treated cows were fourfold longer (P<0.01) than embryos from nontreated cows. In addition, the uterine fluid recovered from P4-treated cows, showed a six-fold higher concentration of IFNτ than the uterine fluid from non-treated cows (Wallace et al, 2011). …”
Section: Role Of Progesterone On Embryo Development and Survivalmentioning
confidence: 99%
“…In animal models, systemic administration of hCG at the time of embryo transfer significantly increases pregnancy rate. 10 Intrauterine hCG injection is associated with significant proimplantation changes of the endometrium during the window of receptivity in normal cycling baboons, and induces a favourable uterine environment for embryo implantation. 11…”
Section: Introductionmentioning
confidence: 99%
“…7,9 In animal models, systemic administration of hCG at the time of embryo transfer significantly increases pregnancy rate. 10 Intrauterine hCG injection is associated with significant proimplantation changes of the endometrium during the window of receptivity in normal cycling baboons, and induces a favourable uterine environment for embryo implantation. 11 Intrauterine injection with hCG (500 IU/ ml) prior to embryo transfer significantly improves rates of implantation and pregnancy in IVF/ICSI (intracytoplasmic sperm injection).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, compared with control, the numerical increase (8%) in pregnancy rate on Day 63 of hCG treatment can be of economic interest. At experiment design, we estimated an increase in pregnancy rate in the range of 5% to 20% based on previous (Chagas e Silva and Lopes-da-Costa, 2005) and published (Nishigai et al, 2002;Wallace et al, 2011) results. Treatment with hCG induced the formation of secondary CL and a significant increase in plasma P 4 concentrations.…”
Section: Discussionmentioning
confidence: 99%